Bukti dan Prosedur dalam Kasus Zina Menurut Fiqih Jinayah dalam Perspektif Pendidikan Agama Islam - Ema Dusti Tatri; Ahmad Suradi; Hengki Satrisno; Ningsi Ningsi; Dhaqi Rotul Mukasafah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2025)
This study aims to examine in depth the evidence and procedures in adultery cases according to Islamic jurisprudence (fiqh jinayah), as well as their relevance from the perspective of Islamic Religious Education (PAI). Adultery is a serious crime that falls under the category of hudud, with sanctions determined by Allah SWT. Through library research methods, this study analyzes various classical and contemporary literature, including the Qur'an, hadith, and fiqh books such as Al-Mughni by Ibn Qudamah and Al-Fiqh al-Islami wa Adillatuhu by Wahbah Az-Zuhaili. The results of the study indicate that the proof of adultery in Islamic jurisprudence is very strict and based on the principle of justice, with the requirement of four just male witnesses or a voluntary confession from the perpetrator. The principle of caution is applied to avoid slander or errors in sentencing. Apart from that, the values ​​in jinayah fiqh contain educational and moral functions that are important for the development of Islamic education, especially in forming the character of students who uphold honesty, responsibility and personal purity. This study confirms that Islamic law is not only repressive, but also functions as an instrument of moral and social education that upholds justice and maintains human honor.